Preparation Of Kuantan Bauxite For Rare Earth Elements Extraction - Rozaly, Muhammad Rushaidi Mohd (Universiti Sains Malaysia, 2017)
Bayer process is a process of extracting alumina from bauxite. This process involves leaching of bauxite with hot concentrated sodium hydroxide. In this project, the characterization of bauxite sample obtained from Kuantan was done. The bauxite sample contain Al2O3 in the majority at 53.10%, Fe2O3 at 36.88%, TiO2 at 5.35%, SiO2 at 3.87%, scandium at 26 ppm, lanthanum at 21.8 ppm and cerium at 19.8 ppm. Alkaline leaching of bauxite was done in an autoclave pressure reactor at 145°C with 5.0 M sodium hydroxide under a soaking time of 2 hours with a rate of temperature rise at 4°C per minute. The recovery of aluminium was recorded at 12.54% due to the low concentration of sodium hydroxide and low soaking period. The red mud produced was then subjected to aeration leaching with 0.37 M ammonium chloride solution at temperature 70°C with solid to liquid ratio of 1 to 4. The residue after reaction ended was found to contain higher iron from 38.54% to 42.22%. This was most probably due to the high alkalinity of red mud at pH 10-12 that cause ammonium chloride unable to neutralize it and convert iron into soluble species which are favorable at lower pH. The aeration of Oxygen also could be considered as a contributor to the precipitation of iron as it seems from the XRF result the aeration promotes precipitation of iron oxides more than precipitation of other metals.